Partial Replacement of Limestone and Silica Powder as a Substitution of Cement in Lightweight Aggregate Concrete - Zareei, Seyed Alireza; Ameri, Farshad; Dorostkar, Farzan; Shiran, Shahriar (Civil Engineering Journal, 2017)
With increasing trends towards the broader usage of concrete and warning depletion of natural resources of aggregates, it seems reasonable to find mineral additives or binding materials of different types as ingredient of concrete.Â  Accordingly, wide usage of light weight concrete lies on some main structural applications as reduction of total dead, seismic loads, environmental pollution, and labour cost. This paper tries to investigate the properties of light weight blended concrete containing lime stone powder (LP), micro-silica (MS), pumice, and leca in various proportioning rateing as a partial replacements of cement. Utilization of these additives on the compressive strength, tensile strength, water absorption coefficient, acid resistance, and impact resistance examined experimentally in various curing conditions at the ages of 7 and 28 days to evaluate the combined effect of micro-silica and lime stone incorporation on strength and durability properties of light weight concrete, along with introduction of optimum replacements. For this purpose, 10 lime-stone based concrete mixtures were prepared with proportions from 0 to 20%, and constant values of 10% micro-silica and w/c ratio. From the results, it was indicated that addition of lime stone powder in concrete reduces short-term properties as well as the compressive strength. Optimum levels of powder replacements can serve as sustainable and durable concrete, also environmental and economic benefits.